1982
DOI: 10.1007/bf00341252
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial and orbital hydatid cysts

Abstract: Parasitic diseases involving brain and orbit are relatively rare in Tunisia; the most frequently encountered is the hydatid cyst, 55 examples of which were seen since CT scanning was introduced into Tunisia 2 years ago. Various aspects of the intracerebral and orbital hydatid cysts are reported and a tentative classification is made based on characteristics revealed by CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Analysis of records showed that out of 9 pediatric cases, only 4 cases had unruptured evacuation, giving a 44% rate of hydatid birth. Comparing this rate in the pre-CT era with a 70% intact removal rate (14 patients) in 20 pediatric cases operated on within the next 20 years – mostly in the CT era – reveals the invaluable place of high-technology diagnosis in neurosurgery [49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65]. Only 1 case out of 14 with CT had a misdiagnosed preoperative lesion (extradural retroclival hydatid cyst), as published in 1994 by Canbolat et al [33].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of records showed that out of 9 pediatric cases, only 4 cases had unruptured evacuation, giving a 44% rate of hydatid birth. Comparing this rate in the pre-CT era with a 70% intact removal rate (14 patients) in 20 pediatric cases operated on within the next 20 years – mostly in the CT era – reveals the invaluable place of high-technology diagnosis in neurosurgery [49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65]. Only 1 case out of 14 with CT had a misdiagnosed preoperative lesion (extradural retroclival hydatid cyst), as published in 1994 by Canbolat et al [33].…”
Section: Discussionmentioning
confidence: 99%
“…Orbital hydatids are typically unilocular, hypodense, nonenhancing cysts [7,8,13,14] and these diagnostic studies demonstrate a well-circumscribed cystic mass in all patients. Fine peripheral rim enhancement following contrast administration is often well documented in CT and MRI [7,8,13,14] . At present, orbital MRI has proved to be a very useful diagnostic tool to rule out other cystic lesions with less water content in spite of its limited use due to high cost in endemic areas [2] .…”
Section: Discussionmentioning
confidence: 78%
“…Immunodiagnostic tests for an isolated orbital hydatid cyst are almost always negative [13]. In this case, though the age of the patient was atypical, there was a typical clinical presentation and location of the cyst, an eosinophilia, a positive indirect haemagglutination test for hydatid disease and disseminated, similar, anechoic cystic masses in the liver, lung, spleen and orbit on imaging studies; based on these findings, the diagnosis of disseminated hydatid cyst was seriously considered before surgery.…”
Section: Discussionmentioning
confidence: 99%